Siberian sturgeon multi-tissue reference transcriptome database. (25th November 2020) - Klopp, Christophe; Cabau, Cédric; Greif, Gonzalo; Lasalle, André; Di Landro, Santiago; Vizziano-Cantonnet, Denise
Abstract: Motivation: Siberian sturgeon is a long lived and late maturing fish farmed for caviar production in 50 countries. Functional genomics enable to find genes of interest for fish farming. In the absence of a reference genome, a reference transcriptome is very useful for sequencing based functional studies. Results: We present here a high-quality transcriptome assembly database built using RNA-seq reads coming from brain, pituitary, gonadal, liver, stomach, kidney, anterior kidney, heart, embryonic and pre-larval tissues. It will facilitate crucial research on topics such as puberty, reproduction, growth, food intake and immunology. This database represents a major contribution to the publicly available sturgeon transcriptome reference datasets. Availability: The database is publicly available at http://siberiansturgeontissuedb.sigenae.org Supplementary information: Supplementary data are available at Database online.